Zmiana systemu subsydiowania budownictwa mieszkaniowego jako czynnik poprawy sytuacji mieszkaniowej rodziny - Michalik, Witold (Wydział Prawa i Administracji UAM, 1985)
The acute deficit of apartments and the resulting difficult housing conditions are not only a grave distress for many families, including the young ones, but are also leading to disadvantages in a general social and economic scale. Therefore using all available instruments for improving that situation is indispensable. It also concerns a change in a system of housing industry subsidies, in order to increase the share of population's financial resources in investments in that industry and a simultaneous change in criteria of granting social assistance in favor of the subjective and not objective directioning of it. That proposition can raise certain resistance in some circles of the society used to a fallacious thesis of the egalitarian character of the previously applied system of grants, its change seems to be socially justified and economically necessary. It can bring about several positive effects in the scope of improvement of the housing conditions. Those would be: the increase in housing construction, .more extensive social housing protection for the most necessitous families (young married couples, the poorest families).
Change in a system of housing industry subsidies as the factor improving housing situation of a family